2019
DOI: 10.1088/1361-6560/ab18bf
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent inverse treatment planning via deep reinforcement learning, a proof-of-principle study in high dose-rate brachytherapy for cervical cancer

Abstract: Inverse treatment planning in radiation therapy is formulated as solving optimization problems. The objective function and constraints consist of multiple terms designed for different clinical and practical considerations. Weighting factors of these terms are needed to define the optimization problem. While a treatment planning optimization engine can solve the optimization problem with given weights, adjusting the weights to yield a high-quality plan is typically performed by a human planner. Yet the weight-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 64 publications
0
93
0
Order By: Relevance
“…Physicians just need to select the plan that has the preferred trade‐off. Another way is to use artificial intelligence to build and train a virtual planner to develop a human‐level intelligence on how to automatically adjust the priorities based on the intermediate plan quality . Our future work is to take the latter way to learn the physicians’ preferred trade‐offs from previously treated patient cases and automate the fine‐tuning process.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians just need to select the plan that has the preferred trade‐off. Another way is to use artificial intelligence to build and train a virtual planner to develop a human‐level intelligence on how to automatically adjust the priorities based on the intermediate plan quality . Our future work is to take the latter way to learn the physicians’ preferred trade‐offs from previously treated patient cases and automate the fine‐tuning process.…”
Section: Discussionmentioning
confidence: 99%
“…In MCO, a plan pool is constructed by generating plans with various trade-offs on Pareto surfaces (Craft et al 2006, Teichert et al 2011. Similar studies can also be found in brachytherapy (van der Meer et al 2018, Shen et al 2018, Zhou et al 2017, Cui et al 2018a, Cui et al 2018b.…”
Section: Introductionmentioning
confidence: 85%
“…), TCP/NTCP models to estimate the clinical effect of a dose deviation, and tools to pinpoint the its most likely cause. Such tools could employ artificial intelligence as already evaluated for treatment planning optimization [64] and inter-fraction adaptation [65] .…”
Section: Requirements and Future Directions For Research Developmentmentioning
confidence: 99%